Genome-Wide Identification and Expression Analysis of NRAMP Family Genes in Soybean (Glycine Max L.) - Qin, Lu; Han, Peipei; Chen, Liyu; Walk, Thomas C.; Li, Yinshui; Hu, Xiaojia; Xie, Lihua; Liao, Hong; Liao, Xing (Frontiers in Plant Science, 2017)
The NRAMP (natural resistance-associated macrophage protein) family of genes has been widely characterized in organisms ranging from bacteria to yeast, plants, mice, and humans. This gene family plays vital roles in divalent metal ion transport across cellular membranes. As yet, comprehensive analysis of NRAMP family genes has not been reported for soybean. In this study, bioinformatics analysis was conducted to identify 13 soybean NRAMP genes, along with their gene structures, phylogenetic relationships and transmembrane domains. Expression analysis suggests that GmNRAMP genes function in numerous tissues and development stages. Moreover, soybean NRAMP genes were differentially regulated by deficiencies of N, P, K, Fe, and S, along with toxicities of Fe, Cu, Cd, and Mn. These results indicate that GmNRAMP genes function in many nutrient stress pathways, and might be involved in crosstalk among nutrient stress pathways. Subcellular localization analysis in Arabidopsis protoplasts confirmed the tonoplast or plasma membrane localization of selected soybean NRMAP proteins. Protein-protein interaction analysis found that the networks of 3 GmNRAMP proteins which putatively interact with nodulin-like proteins, almost distinct from the network that is common to the other 10 soybean NRAMP proteins. Subsequent qRT-PCR results confirmed that these 3 GmNRMAP genes exhibited enhanced expression in soybean nodules, suggesting potential functions in the transport of Fe or other metal ions in soybean nodules. Overall, the systematic analysis of the GmNRAMP gene family reported herein provides valuable information for further studies on the biological roles of GmNRAMPs in divalent metal ion transport in various soybean tissues under numerous nutrient stresses and soybean-rhizobia symbiosis.